2016
DOI: 10.1057/s41261-016-0037-5
|View full text |Cite
|
Sign up to set email alerts
|

Supervisory boards, financial crisis and bank performance: do board characteristics matter?

Abstract: Failures in governance, especially in regard to boards of directors, have been blamed for the [2007][2008] financial crisis. The increased public scrutiny regarding the actions and role of the board of directors in banks, following the crisis, inspires to examine whether and to what extent the characteristics of banks' boards influence their performance in the crisis. Using a sample of 72 publicly listed European banks, we find that banks with more independent and busy boards experienced worse stock returns du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
42
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 101 publications
(145 reference statements)
8
42
1
1
Order By: Relevance
“…This change has now been extended to all banks under "Art 47" of the new banking law. Other authors found results similar to ours (Pathan and Faff 2013;Fernandes et al 2016;Ataur and Jahurul 2018).…”
Section: 0000supporting
confidence: 89%
See 2 more Smart Citations
“…This change has now been extended to all banks under "Art 47" of the new banking law. Other authors found results similar to ours (Pathan and Faff 2013;Fernandes et al 2016;Ataur and Jahurul 2018).…”
Section: 0000supporting
confidence: 89%
“…They suggested that an optimal combination of independent and non-independent directors would be more effective in securing bank value than excessively independent advice. In a recent study by Fernandes et al (2016) on the performance of banks during the financial crises of 2007-2008, their results revealed that the most successful banks during the crisis had big independent boards. Based on the literature regarding the impact of board independence on the efficiency of banking activity, we make the following assumption: H 3 : A high percentage of independent directors on the board of directors is linked to higher performance.…”
Section: Independent Directors and Bank Performancementioning
confidence: 99%
See 1 more Smart Citation
“…This study used a sample of CEOs from publicly-listed US banks during the period from 1992 to 2011. Another study from Fernandes et al (2017b) emphasized that directors' qualifications may affect banks' performance, and if the level of directors' qualifications are higher, they will be capable of making better corporate decisions. The previous aspect is more relevant for banks in which the complexity of their activity is higher than others.…”
Section: Directors' Educational Level and Banks' Financial Performancementioning
confidence: 99%
“…The global financial crisis (GFC) of the last decade has been described as the most severe crisis since the Great Depression of 1940 (Fernandes, Farinha, Martins, & Mateus, 2016). However, different countries had various experiences and method for approaching their banking recapitalization and how they affect banks performance.…”
Section: Introductionmentioning
confidence: 99%